2022
DOI: 10.3390/foods11131963
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pesticide Residues Occurrence in Random Samples of Organic Fruits and Vegetables Marketed in Poland

Abstract: In recent years, organic food, produced with the use of natural means and production methods, has been gaining more and more popularity among consumers. This is due, inter alia, to their belief that it is more abundant in health-promoting bioactive compounds and safer than conventional food. Consumers are increasingly aware of the harmfulness of plant protection products used in intensive agriculture, which are not allowed in organic production. At the same time, it is reported that a certain share of organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…However, it is not optimistic that some organic products on the EU market are contaminated with pesticides, which is a cause for concern among consumers. Kazimierczak et al 32 analyzed 96 samples of organic agricultural products sold in the Polish market for pesticide multiresidue analysis and found that 7.3% of the samples (2 potatoes and 5 carrots) were contaminated with pesticides, and chlorpyrifos was detected above the MRL (0.1 mg kg –1 ) for one of the carrot samples. Apart from the use of unapproved pesticides, the probable cause was the transfer of pesticides that had previously accumulated in the soil to the plants.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is not optimistic that some organic products on the EU market are contaminated with pesticides, which is a cause for concern among consumers. Kazimierczak et al 32 analyzed 96 samples of organic agricultural products sold in the Polish market for pesticide multiresidue analysis and found that 7.3% of the samples (2 potatoes and 5 carrots) were contaminated with pesticides, and chlorpyrifos was detected above the MRL (0.1 mg kg –1 ) for one of the carrot samples. Apart from the use of unapproved pesticides, the probable cause was the transfer of pesticides that had previously accumulated in the soil to the plants.…”
Section: Resultsmentioning
confidence: 99%
“…Tragically, the utilization of the lion’s share of pesticides postures a threat to the characteristic environment [ 39 , 40 , 41 ], and their inappropriate utilization leads to pesticide buildups in crops and nourishment items [ 42 ]. For human health, primary and derived agricultural products are the most real source of pesticide residues that are found in all agroecosystems [ 43 , 44 ]. Poorly tracked pesticide residues replenish concentrations of organic xenobiotics, poisoning ecosystems [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Omeje et al. (2022) found several organophosphorus and organochlorine pesticide residues in fresh fruits in a Nigerian market, some of them are even legally prohibited, such as linuron, propiconazole, and chlorpyrifos (Kazimierczak et al., 2022). In addition to fresh fruits, pesticides were also detected in some processed fruit products.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Drabova et al (2022) detected 38 different pesticide residues in citrus in a Czech market, with thiazide and fenbutatin oxide exceeding the maximum residue limits (MRLs). Omeje et al (2022) found several organophosphorus and organochlorine pesticide residues in fresh fruits in a Nigerian market, some of them are even legally prohibited, such as linuron, propiconazole, and chlorpyrifos (Kazimierczak et al, 2022). In addition to fresh fruits, pesticides were also detected in some processed fruit products.…”
Section: Introductionmentioning
confidence: 99%